Optimization of Cryogenic Process Parameters for the Minimization of Surface Residual Stress in Pure Iron Using Taguchi Design. (2nd November 2021) - Zheng, Meng; Kong, Jinxing; Sun, Yuwen
Abstract : The plastic deformation produced in the machining process can cause residual stress. As an effective way to control the residual stresses, the cryogenic process is used in modern industries such as aerospace, automobile, and shipping industry. Focusing on the minimization of surface stress in the cryogenic process of pure iron, the Taguchi design is used in this paper. The effect of cryogenic temperature (77–193 K), holding time (8–24 H), cooling rate (2–6 K/min), and warming-up rate (0.5–1.5 K/min) on surface residual stress is discussed and the optimal combination of cryogenic parameters is obtained using signal-to-noise (S/N) ratios. To overcome the weakness of the Taguchi method that cannot calculate stresses, an exponential model to predict residual stresses considering cryogenic parameters is developed. The coefficients of this mathematical model are obtained using multilinear regressive analysis based on the database of the Taguchi experiment. After this, the optimization process is conducted with this model using the genetic algorithm (GA). The optimized results using both ways coincide with each other. The optimal cryogenic parameters are obtained, i.e., cryogenic temperature of 193 K, holding time of 24 h, cooling rate of 2 K/min, and warming-up rate of 0.5 K/min. When the optimum cryogenic parameters are used, the surface residual stress is reduced by 42.9% in the cutting direction and 46.2% in the feeding direction. The method can be applied to the actual machining engineering to realize the low-stress control on the cutting surface.